Study of physicochemical aspects of hydrogen sulfide adsorption on a composite material from water treatment sludge - Iliev Iliya; Filimonova Antonina; Vlasova Alena; Kamalieva Ruzina; Beloev Ivan (E3S Web of Conferences)
The adsorption method is widely used to neutralize industrial emissions, allowing almost complete extraction of impurities from gas flows. The advantages of waste-based adsorbents include low production costs, no need for complex disposal, high adsorption capacity due to the content of metal ions, and the possibility of waste disposal. In this study, a composite material for hydrogen adsorption is proposed, consisting of sludge from a thermal power plant water treatment plant and metal oxides of manganese, calcium, zinc, and iron, chemically interacting with hydrogen sulfide. The physicochemical aspects of the adsorption process for the developed composite material were studied: sulfur capacity, required contact time of the adsorbate with the adsorbent, efficiency, integral and differential heat of adsorption.